Elaboração e avaliação de tecnologia educacional sobre cuidados no pré-natal - Silva, Bruna Carneiro (2019)
Introduction: Pregnancy is a unique event in a woman's life marked by psychological, hormonal and physical changes that can lead to fears, doubts, anxieties and uncertainties about so many changes. Educational technologies are tools that help in the teaching-learning process and can minimize risks and collaborate with the pregnant women care. This study is aligned with the line of research caring for nursing in the human development process and sought to combine the benefits of educational technologies to meet the demand of the institution in which the master's student works, in order to collaborate in the health education of pregnant women.Objectives: Identify the content of the comic with the target audience; Develop the comic on prenatal care; Evaluate educational technology with the target audience. Method: This is a methodological study that was developed in three stages: step 1 - exploratory study: identification of comic content; step 2 - process of elaboration of the comic; and step 3 - technology assessment with the target audience. To identify the content, groups were made with pregnant women and the non-directive interview technique was used. The groups took place in weekly meetings, between March and May 2018, in which 34 pregnant women participated. The groups were recorded, transcribed and the data analyzed and categorized according to Bardin. To evaluate the almanac, 41 pregnant women participated, who answered an evaluation questionnaire with the criteria: objectives, organization, writing style, appearance and motivation. The agreement rate of 80% was adopted. Results: The printed educational technology, entitled Pregnant Woman's Almanac, is made up of 40 pages that contain comic books and wordpuzzle games, maze, spot the differences, among others and addresses the themes of pregnancy discovery, prenatal care and childbirth. The prenatal theme presents guidelines on feeding; food hygiene; exercise practice; high blood pressure and gestational diabetes; sexually transmitted infections; toxoplasmosis; Dengue / Zika / Chikungunya; vaccination and use of vitamins. The pregnant women evaluated the technology as easy to understand, explanatory, clear language, attractive and comprehensive, capable of motivating the maintenance of good pregnancy practices, with a minimum agreement of 95.1%. Products: Pregnant woman's almanac. Final considerations:The almanac stimulates in a creative and playful way, the reflection of pregnant women for prenatal care and facilitates the learning process, through the use of innovative educational technology, which takes into account the information and experiences of pregnant women, because it was developed in partnership with the service and the target population. It has the potential to generate impact and applicability at local, regional and national level, as it will be made available in pdf on a virtual platform. After the copyright registration Almanac will be returned to the health department, strengthening the humanization policy of assistance to prenatal care.The Almanac is a health education strategy on prenatal care, and it is important that the health professional enables discussions taking into account the ability of each family member to understand, and also to associate the use of technology with verbal guidance that can elucidate the aspects treated in the comic books and games presented in the almanac